Integrating Local Culture Into 3D Learning Media: Development of A Mora’a-Based Pop-Up Book For Elementary Science and Social Studies - Andini Aulia Salsabila; Muhammad Aqil; Surahman Wilade; Rizal Rizal; Ryan Andhika Pratama (Journal of Innovation and Research in Primary Education, 2026)
The integration of local culture into learning media is increasingly recognized as a strategy to make elementary education more meaningful and contextually relevant. However, many instructional materials used in Science and Social Studies (IPAS) learning remain abstract and minimally connected to students’ cultural environments. This study aimed to develop a Mora’a-based pop-up book as a three-dimensional (3D) learning medium and to examine its validity, practicality, and potential contribution to improving elementary students’ IPAS learning outcomes. The study employed a research and development design using the ADDIE model, limited to the stages of analysis, design, development, and implementation. The product was validated by media and content experts, followed by limited and field trials involving fourth-grade students. Data were collected through validation sheets, response questionnaires, observations, and pretest–posttest assessments. The expert validation results indicated that the pop-up book met the criteria of high validity in terms of content, visual design, and usability. Student and teacher responses showed that the media was practical and engaging for classroom use. Learning outcome data demonstrated an improvement in students’ posttest scores compared to pretest results after using the Mora’a-based pop-up book. These findings suggest that integrating local cultural values into interactive 3D learning media can support more meaningful IPAS learning while simultaneously fostering students’ appreciation of their cultural heritage. The study contributes to the development of culturally responsive and visually engaging instructional media for primary education.